Drainage During Endoscopic Thyroidectomy - Chen, Gao-xiang; Li, Cheng; Zhang, Hai (Journal of the Society of Laparoendoscopic Surgeons, 2019)
Conventional cervical drainage tubes are placed crossing the suprasternal fossa during endoscopic thyroidectomy. In our clinical experience, some patients show shallow or absent suprasternal fossa, which affects the cosmetic outcome in the patient. Therefore, this study aimed to assess the feasibility and significance of restoring the suprasternal fossa by changing the position of neck drainage tubes. A total of 117 female patients were enrolled and divided into 2 groups, including 59 and 58 individuals in the Conventional (conventional anterior neck region negative pressure drainage) and Improvement (improved method with a negative pressure drainage) groups. Then, restoration of the suprasternal fossa in all subjects was observed at 1 day postsurgery, the day of extubation, and 3 months postoperatively. In addition, drainage volume, the time to extubation, and abnormal neck sensations were compared between the groups. Compared with the Conventional group, the Improvement group showed improved restoration of the suprasternal fossa, with the patients more satisfied with the cosmetic outcome. However, operation time, postoperative drainage volume, and extubation time were not significantly different between the 2 groups. In endoscopic thyroidectomy via the chest and breast approach, using the new drainage technique described here could yield improved restoration of the suprasternal fossa, ameliorating the cosmetic outcome and patient satisfaction.